Exhibit Palace Housing the Alameda-Contra Costa Counties $140,000 Display at the World's Fair
I was visitor no. 394 at the Alameda-Contra Costa Counties Exhibit at Golden Gate International Exposition on Treasure Island. When you come to the Fair be sure and visit this wonderful exhibit, located in center of the California group of buildings.